2009
DOI: 10.1007/s12274-009-9038-3
|View full text |Cite
|
Sign up to set email alerts
|

Au-Ag alloy nanoporous nanotubes

Abstract: Metallic nanostructures with hollow interiors or tailored porosity represent a special class of attractive materials with intriguing chemicophysical properties. This paper presents the fabrication of a new type of metallic nanoporous nanotube structure based on a facile and effective combination of nanocrystal growth and surface modifi cation. By controlling the individual steps involved in this process, such as nanowire growth, surface modifi cation, thermal diffusion, and dealloying, one-dimensional (1-D) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 30 publications
1
51
0
1
Order By: Relevance
“…By combining with other synthesis or nanofabrication methods including polyol process, templated process, solid-state dewetting, and different nanolithography techniques, Au-Ag alloys can be formed in many specific forms, and after dealloying, the nanoporous gold can be obtained in the corresponding forms, including the forms of nanotubes [38], nanowires [39], nanoparticles [17,40,41], hollowed nanospheres [42], nanobowls [43], nanodisks [44,45], ordered array of nanoparticles and nanodisks [46][47][48].…”
Section: Fabrication Of Gold Nanosponges and Hybrid Nanospongesmentioning
confidence: 99%
“…By combining with other synthesis or nanofabrication methods including polyol process, templated process, solid-state dewetting, and different nanolithography techniques, Au-Ag alloys can be formed in many specific forms, and after dealloying, the nanoporous gold can be obtained in the corresponding forms, including the forms of nanotubes [38], nanowires [39], nanoparticles [17,40,41], hollowed nanospheres [42], nanobowls [43], nanodisks [44,45], ordered array of nanoparticles and nanodisks [46][47][48].…”
Section: Fabrication Of Gold Nanosponges and Hybrid Nanospongesmentioning
confidence: 99%
“…An alternate strategy for the preparation of nanoporous nanowires that does not involve electrodeposition entails the deposition of gold on a silver nanowire formed via a polyol process. The Au:Ag alloy is formed when the surface gold atoms interdiffuse with the underlying silver atoms at an elevated temperature [57].…”
Section: Alloy Preparationmentioning
confidence: 99%
“…Nanopores developed only during delithiation, involving the aggregation of vacancies produced by lithium extraction, similar to the formation of porous metals in dealloying. Shui et al Similarly, Gu et al 87,88 also reported a kind of wellde¯ned 1D Ag-Au alloy nanotubes. In their work, a three-step nanocrystal growth and structure-tailoring process was involved.…”
Section: Other Nontemplate-assisted Methodsmentioning
confidence: 94%